Long-run money demand in the new EU Member States with exchange rate effects - Christian Dreger; Hans-Eggert Reimers; Barbara Roffia (European Central Bank (ECB), 2006)
Generally speaking, money demand models represent a natural benchmark against which monetary developments can be assessed. In particular, the existence of a well-specified and stable relationship between money and prices can be perceived as a prerequisite for the use of monetary aggregates in the conduct of monetary policy. In this study a money demand analysis in the new Member States of the European Union (EU) is conducted using panel cointegration methods. A well-behaved long run money demand relationship can be identified only if the exchange rate as part of the opportunity cost is included. In the long-run cointegrating vector the income elasticity exceeds unity. Moreover, over the whole sample period the exchange rates vis-à-vis the US dollar turn out to be significant and a more appropriate variable in the money demand than the euro exchange rate. The present analysis is of importance for the new EU Member States as they are expected to join in the future years the euro area, where money is deemed to be highly relevant - within the two-pillar monetary strategy of the European Central Bank (ECB) - in order to detect risks to price stability over the medium term.
Keywords: C23; E41; E52; 330; exchange rate; Money demand; new EU member states; Panel Cointegration; Geldnachfrage; Wechselkurs; Kointegration; EU-Mitgliedschaft